SAT0073 Arterial Hypertension In Rheumatoid Arthritis Without Cardiovascular Disease: High Prevalence, Low Awareness, Poor Control And Increased Vascular Damage-Associated "White Coat" Phenomenon. (23rd January 2014) - Protogerou, A.; Zampeli, E.; Konstantonis, G. D.; Arida, K.; Panagiotakos, D. B.; Argyris, A. A.; Pitsavos, C.; Kitas, G. D.; Sfikakis, P. P.
Abstract : Background: Rheumatoid arthritis (RA) is associated with a high cardiovascular disease (CVD) risk, whereas the prevalence and significance of arterial hypertension, the major modifiable CVD risk factor, is still a matter of investigation in these patients (1 -3 ). Objectives: To examine the characteristics of arterial hypertension in a typical, contemporary RA cohort. Methods: In 214 consecutive RA patients free of CVD (aged 58.4±12.3 years, 82% women) we conducted a comprehensive study including: (i) guideline-based (4 ) assessments of office and out-of-office blood pressure (BP) (7-days home BP monitoring or 24hr ambulatory BP monitoring); (ii) vascular studies to detect end-organ damage. Office BP assessments in a 1:1 age- and gender-matched general population group were used for comparison. Results: The prevalence of known hypertension in RA was 44%. Of the remaining patients, 2 out of 5 had systolic BP/diastolic BP higher than 139/89 mmHg at office, contributing to a double prevalence than the general population (67% vs. 34%). Out-of-office and/or ambulatory 24-hourBP measurements revealed an actual 54% prevalence of hypertension in RA, i.e. an additional 10% of patients was unaware of having hypertension. Hypertension was positively associated with age and body mass index, and inversely with the use of biologic drugs. Of patients with known hypertension 29% were not well controlled. Overall, almost 1 out of 5 presented the 'white coat' phenomenon, irrespective of antihypertensive drug use. Interestingly, an intermediately compromised vascular phenotype in terms of aortic stiffness, carotid hypertrophy and ankle-brachial index was evident in 'white coat' phenomenon patients, lying between patients with sustained normotension and sustained hypertension. Conclusions: Accurate and prompt diagnosis, and effective treatment of arterial hypertension is of key importance in RA and should be placed at the top of both clinical and research agenda for CVD risk reduction. References: Aviña-Zubieta JA, et al. Risk of Cardiovascular Mortality in Patients With Rheumatoid Arthritis: A Meta-Analysis of Observational Studies. Arthritis Rheum 2008;59:1690-7. Panoulas VF, et al. Prevalence and associations of hypertension and its control in patients with rheumatoid arthritis. Rheumatology 2007; 46:1477-82. Liao KP, Solomon DH. Traditional cardiovascular risk factors, inflammation and cardiovascular risk in rheumatoid arthritis. Rheumatology 2013; 52:45-52. Mancia G, et al.; ESH-ESC Task Force on the Management of Arterial Hypertension. J Hypertens 2007; 25:1751-62. Disclosure of Interest: None Declared